2018
DOI: 10.3390/nu10101559
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Fatty Acids and Cardiometabolic Health

Abstract: Cardiovascular disease (CVD) is a major cause of mortality. The effects of several unsaturated fatty acids on cardiometabolic health, such as eicosapentaenoic acid (EPA) docosahexaenoic acid (DHA), α linolenic acid (ALA), linoleic acid (LA), and oleic acid (OA) have received much attention in past years. In addition, results from recent studies revealed that several other uncommon fatty acids (fatty acids present at a low content or else not contained in usual foods), such as furan fatty acids, n-3 docosapenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 104 publications
0
30
0
2
Order By: Relevance
“…The effects were inconsistent for bladder cancer [42], breast cancer [43], ovarian cancer [44] and non-Hodgkin's lymphoma [40] because of the different type or dose of milk. No association was found between milk consumption and endometrial cancer [45], esophageal squamous cell carcinoma [46], hepatocellular carcinoma [47], lung cancer [48], follicular lymphoma [40], small lymphocytic lymphoma/chronic lymphocytic leukemia [40] and pancreatic cancer [49]. [57].…”
Section: Cancer Outcomesmentioning
confidence: 96%
“…The effects were inconsistent for bladder cancer [42], breast cancer [43], ovarian cancer [44] and non-Hodgkin's lymphoma [40] because of the different type or dose of milk. No association was found between milk consumption and endometrial cancer [45], esophageal squamous cell carcinoma [46], hepatocellular carcinoma [47], lung cancer [48], follicular lymphoma [40], small lymphocytic lymphoma/chronic lymphocytic leukemia [40] and pancreatic cancer [49]. [57].…”
Section: Cancer Outcomesmentioning
confidence: 96%
“…The review also however noted concerns on potential safety of CLA with reports of increased insulin resistance and lipodystrophy in animal models, in addition to some adverse lipid and C-RP responses in clinical studies. In line with this note of caution, several recent reviews have concluded that many positive outcomes reported in animal models or in vitro have not been adequately replicated in clinical trials ( 88 , 89 ). The 2018 review by Li et al reported the lack of clinical data for hard CV endpoints.…”
Section: Cardiometabolic Effects Of Dairy Macro- and Micro-nutrients:mentioning
confidence: 99%
“…The effects of PUFAs on cardiometabolic health, such as α-linolenic, linoleic, and oleic acids, have received much attention in past years (Li et al 2018). These compounds probably act as antioxidants, protecting cell membranes from the negative impact of free radicals.…”
Section: Introductionmentioning
confidence: 99%